Guillain-Barré syndrome associated with SARS-CoV-2 infection: a scoping review - Medeiros,Kleyton Santos de (2021)
SUMMARY BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections can affect the nervous system, triggering problems such as the Guillain-Barre Syndrome (GBS), an association that can bring complications to the patient. OBJECTIVE: This scoping review aimed to clarify the clinical features and analyze patients with GBS associated with SARS-CoV-2 infection, looking at morbidity, mortality, and neurological outcomes. SEARCH STRATEGY: The search was conducted through Medline, Web of Science, Embase, CINAHAL, Latin-American and Caribbean Literature in Health Sciences (LILACS), clinicaltrials.gov, SCOPUS, and the Cochrane Central Register of Controlled Trials. SELECTION CRITERIA: Observational studies, published after 2019, describe patients with GBS associated with SARS-CoV-2 infection. There were no language restrictions while selecting the studies. DATA COLLECTION AND ANALYSIS: Three authors, Kleyton Santos de Medeiros, Luíza Thomé de Araújo Macêdo, and Wederson Farias de Souza, independently screened the search results using titles and abstracts. Duplicate studies were excluded. The same authors then went through the entire text to determine whether the studies met the inclusion criteria. Discrepancies were resolved by other reviewers, Ana Paula Ferreira Costa, Ayane Cristine Sarmento, and Ana Katherine Gonçalves. Finally, the selection of the studies was summarized in a PRISMA flow diagram. MAIN RESULTS: Main manifestations were fever, coughing, dyspnea, sore throat, ageusia, anosmia, and respiratory failure, in addition to paresthesia of the upper and lower limbs, tetraparesis, facial diplegia, areflexia, asthenia, mastoid pain, acute ataxia, fatigue, numbness, swallowing disorder, and moderate low back pain. CONCLUSION: Coronavirus disease 2019 (COVID-19) can trigger the GBS, despite the few studies on this topic. Patients had clinical manifestations of COVID-19 infection and neurological manifestations characterizing GBS.